Exposure scenario of nanopowders into test-media; 4th International Conference on Nanotechnology - Occupational and Environmental Health, Helsinki, Finland, August 26-29, 2009 - Godymchuk (Godimchuk) A. Yu. Anna Yuryevna (2009, 2009)
В фонде НТБ ТПУ отсутствует